Managing teaching and learning situations at the tertiary level: a qualitative case study of the challenges faced by the academic staff at the international Islamic university, Malaysia - Nik Abdul Rahman , Nik Suryani (s.n, 2012)
Teaching at tertiary level involve a complex and diverse work process. Most higher education faculty received heir advancement of content knowledge but are seldom given the opportunity to integrate this content knowledge with the teaching pedagogy. This fragmentation of practice leaves teachers on their own with the challenge of integrating subject matter knowledge and pedagogy in the contexts of their work.